EMOTIONAL EXPERIENCE WRITING MODEL: AN INTERVENTION FOR ENHANCING PROBLEM-SOLVING SKILLS AMONG ADOLESCENTS WITH SOCIO-EMOTIONAL PROBLEMS IN ORPHANAGES - Jati, Sri Nugroho; Trisnawati, Elly; Sanjani, Resi Raf; Nurmaliza, Tengku Haqy (Jurnal Psikologi, 2023)
This study aims to determine the effectiveness of emotional experience writing (EXPRIT) model in enhancing the problem-solving skills among adolescents with social-emotional problems in orphanages. The EXPRIT model is an intervention based on cognitive psychotherapy that can train adolescents’ socio-emotional problem-solving skills. The prevalence study found that 26.9% had behavioral disorders and 10.2% of emotional disorders of orphans were found in the 10-14 years old age group. Initial interviews conducted for this study indicated that children in the orphanage experienced problems such as difficulties in adapting at their environment in the orphanage and some emotional behavior problems. A total 15 participants from various orphanages were included in a one-group pre-test and post-test experimental design research. Problem-solving skills were assessed using an adapted “Teen Wellness Self-Assessment” scale. The sampling technique used was purposive sampling, and the data were analyzed using the paired sample t-test. The findings demonstrate a significant positive impact of the EXPRIT intervention on enhancing problem-solving skills in orphaned adolescent, t(14) = 4.503, p = .000; Cohen’s d = 1.163, suggesting substantial practical significance with potential implications for addressing socioemotional challenges in this population. Despite its promising results, this current study was limited byits small sample size. These findings highlightthe importance of targeted interventions in addressing the needs of orphaned youth dealing with socio-emotional problems